2021
DOI: 10.1590/1678-5150-pvb-6818
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and disinfectant resistance of Salmonella Heidelberg from Brazilian flocks did not increase for ten years (2006-2016)

Abstract: Salmonella is a major cause of foodborne illness worldwide, and poultry and its derived products are the most common food products associated with salmonellosis outbreaks. Some countries, including Brazil, have experienced an increased prevalence of Salmonella Heidelberg among their poultry flocks. Some isolates have also presented high resistance to antimicrobial agents and persist in the poultry farm environment. This study aimed to compare the susceptibility of S. Heidelberg strains isolated in 2006 with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Whilst some isolates showed elevated MIC to several biocides and resistance to some antibiotics, they remained susceptible to a BKC product (Beier, Andrews, et al, 2021 ; Beier, Byrd et al, 2021 ). Bassani et al ( 2021 ) observed no differences in bacterial susceptibility to BKC or antibiotics in S. Heidelberg isolates over a 10‐year period.…”
Section: Benzalkonium Chloride and Bacterial ‘Resistance’mentioning
confidence: 97%
“…Whilst some isolates showed elevated MIC to several biocides and resistance to some antibiotics, they remained susceptible to a BKC product (Beier, Andrews, et al, 2021 ; Beier, Byrd et al, 2021 ). Bassani et al ( 2021 ) observed no differences in bacterial susceptibility to BKC or antibiotics in S. Heidelberg isolates over a 10‐year period.…”
Section: Benzalkonium Chloride and Bacterial ‘Resistance’mentioning
confidence: 97%
“…A Brazilian comparison of biocide (sodium hypochlorite and benzalkonium chloride) use on AMR of S. Heidelberg isolated from poultry flocks in 2006 with those isolated in 2016 showed no increase in resistance/tolerance over this time period to either biocides or antibiotics (with the exception of tetracycline resistance which showed an increase), suggesting no signs co-selection from biocide use [95].…”
Section: Impact Of Biocides On Amr In Food Animal Productionmentioning
confidence: 95%